Rhetorical Strategy and Linguistics Features in E-Petition Through Change.org - Nurrahma Restia Fatkhiyati; Suharno Suharno (Lingua Cultura, 2019)
The research explored what types and how rhetorical strategy correlated with the linguistics features in e-petitions through Change.org entitled “KPK dalam Bahaya”. The data were e-petitions collected through Change.org. The analysis was holistically descriptive and included in qualitative research. The approach used critical discourse analysis by Fairclough that was using Fairclough’s three-dimensional framework and the strategy of rhetoric by Aristotle. Those theories helped the researcher to find out how the rhetorical strategy and the linguistics features created persuasive meaning. The findings indicate that euphemism, metaphor, connectives, logical connectors, rhetorical questions, and modality support the rhetoric strategy constructing the meaning beyond the words. Through one of the rhetoric strategies, pathos persuades the readers to agree to the argument and sign the e-petitions. Due to the emotional appeals, all of these language instruments help the rhetoric to provoke the readers significantly.